2017
DOI: 10.1155/2017/4907898
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Microsphere Destruction by a Continuous Flow Ventricular Assist Device: An In Vitro Evaluation Using a Mock Circulation Loop

Abstract: Objectives Transthoracic echocardiography (TTE) is fundamental in managing patients supported with ventricular assist devices (VAD). However imaging can be difficult in these patients. Contrast improves image quality but they are hydrodynamically fragile agents. The aim was to assess contrast concentration following passage through a VAD utilising a mock circulation loop (MCL). Methods Heartware continuous flow (CF) VAD was incorporated into a MCL. Definity® contrast was infused into the MCL with imaging befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This means their usefulness in LVAD patients is partially diminished, especially at higher pump speeds. A study conducted by Platts et al showed that when echocardiograms were performed with contrast in LVAD patients, contrast signal intensity has an inverse relationship with pump speed ( 25 ). Despite this, use of contrast agent still improves visualization of structures in LVAD patients to an extent that treatment can be adjusted.…”
Section: Clinical Imaging Monitoring and Evaluationmentioning
confidence: 99%
“…This means their usefulness in LVAD patients is partially diminished, especially at higher pump speeds. A study conducted by Platts et al showed that when echocardiograms were performed with contrast in LVAD patients, contrast signal intensity has an inverse relationship with pump speed ( 25 ). Despite this, use of contrast agent still improves visualization of structures in LVAD patients to an extent that treatment can be adjusted.…”
Section: Clinical Imaging Monitoring and Evaluationmentioning
confidence: 99%